Health knowledge and infection control by event horse owners - Ellis, H.; Kendall, Nigel R.; Kydd, Julia H. (2016)
Infection control and quarantine measures are essential to minimise the impact of equine infectious diseases, but their uptake by equestrians involved with sport horses in the United Kingdom is undocumented. Using a questionnaire, this study aimed to: i) determine the knowledge and practices of eventing equestrians about their horses’ health and the clinical signs of endemic and exotic equine infectious diseases and ii) assess existing infection control and quarantine measures on event horse yards. A questionnaire was designed, piloted and distributed electronically over six weeks. The target respondents were equestrians involved in eventing, including jumping their horses over fences either <100cms or >100cms. Data were described qualitatively and analysed statistically to identify any relationships between selected parameters. A total of 146 responses were analysed. The majority of respondents were female, involved as amateurs in eventing and their veterinary surgeon was the first choice for advice. To assess temperature,owners often used touch, but rectal temperature was taken rarely. The majority of horses were vaccinated against tetanus and influenza but a minority against EHV-1/-4. Most respondents identified the clinical signs of influenza and Streptococcus equi, but were less certain about EHV-1/-4. Only 30.1% of respondents had access to quarantine facilities, which were significantly more likely to be available in professional yards (p=0.043) and in riders competing above the 100cm level (p=0.0003). Professionals competing their horses above 100cm were significantly more likely to have quarantine facilities (p<0.05). A majority of yards with quarantine facilities isolated new horses for 2-4 weeks. Facilities included a separate stable (81.8%) or field (68.2%), but separate equipment (47.7%) and access to disinfectant (36.4%) were available less frequently. In conclusion, amateur equestrians involved in eventing require better education on the routine use of infection control and quarantine measures to minimise the impact of equine infectious diseases and thus strengthen infection control nationally.